2023
DOI: 10.3389/fbioe.2023.1162089
|View full text |Cite
|
Sign up to set email alerts
|

Small extracellular vesicles in breast cancer brain metastasis and the prospect of clinical application

Abstract: Extracellular vesicles (EVs) are nanoscale extracellular particles that have received widespread scientific attention for carrying a variety of biomolecules such as nucleic acids and proteins and participating in the process of intercellular information exchange, making them become a research hotspot due to their potential diagnostic value. Breast cancer is the leading cause of cancer-related death in women, approximately 90% of patient deaths are due to metastasis complications. Brain metastasis is an importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 76 publications
(85 reference statements)
0
3
0
Order By: Relevance
“… 38 Several studies have confirmed the close relationship between distant metastasis in breast cancer and the DNA, RNA, and proteins carried by EVs. 39 , 40 , 41 , 42 A study that made a significant impact discovered a strong correlation between integrins expressed on EVs and organ-specific metastasis in breast cancer. 43 This result suggested that EVs could not only assess metastasis but also provide further information about the specific sites of metastasis based on the molecular expression of EVs.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Several studies have confirmed the close relationship between distant metastasis in breast cancer and the DNA, RNA, and proteins carried by EVs. 39 , 40 , 41 , 42 A study that made a significant impact discovered a strong correlation between integrins expressed on EVs and organ-specific metastasis in breast cancer. 43 This result suggested that EVs could not only assess metastasis but also provide further information about the specific sites of metastasis based on the molecular expression of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is to use naturally derived parAcles with lipid membranes to deliver therapeuAcs across the BBB. Extracellular vesicles (EVs) are small parAcles naturally released from cells that carry and deliver bioacAve molecules as a method of cell-to-cell communicaAon, and EVs from various types of cells have been shown to target tumors and cross the BBB 12,13 . EVs can be classified by mechanism of biogenesis, size, funcAon, or composiAon; examples of EVs classified by biogenesis include exosomes, microvesicles, and apoptoAc bodies 14 .…”
Section: Introduc'onmentioning
confidence: 99%
“…Because of the overlapping size range of microvesicles and exosomes, EVs are oRen characterized as enriched populaAons of small EVs and large EVs rather than pure populaAons 14 . Because EVs can circulate in the bloodstream for a prolonged period of Ame, can cross the BBB 12,13,[15][16][17][18][19][20] , and are manipulable as carriers of drugs, nucleic acids, or nanoparAcles [17][18][19][20][21][22][23][24][25][26][27][28][29] , there is vast potenAal to engineer EVs as imaging or delivery tools to target brain metastases. Previous studies have labeled EVs with superparamagneAc iron oxide (SPIO) nanoparAcles for in vivo tracking using magneAc resonance imaging (MRI) [24][25][26]30,31 and to a lesser extent, magneAc parAcle imaging (MPI) 32 .…”
Section: Introduc'onmentioning
confidence: 99%
“…One possibility is to use naturally derived particles with lipid membranes to deliver therapeutics across the BBB or improve delivery across the BTB. Extracellular vesicles (EVs) are small particles naturally released from cells that carry and deliver bioactive molecules as a method of cell-to-cell communication, and EVs from various types of cells have been shown to target tumors and cross the BBB. , EVs can be classified by mechanism of biogenesis, size, function, or composition; examples of EVs classified by biogenesis include exosomes, microvesicles, and apoptotic bodies . Exosomes are formed by internal budding within a multivesicular body and range in size from 40 to 150 nm in diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the overlapping size range of microvesicles and exosomes, EVs are often characterized as enriched populations of small EVs and large EVs rather than pure populations . Because EVs can circulate in the bloodstream for a prolonged period of time, can cross the BBB, ,, and can be manipulated as carriers of drugs, nucleic acids, or nanoparticles, there is vast potential to engineer EVs as imaging or delivery tools to target brain metastases. Previous studies have labeled EVs with superparamagnetic iron oxide (SPIO) nanoparticles for in vivo tracking using magnetic resonance imaging (MRI) ,, and to a lesser extent, magnetic particle imaging (MPI) .…”
Section: Introductionmentioning
confidence: 99%